Evidence of cryptic diversity in Podarcis peloponnesiacus and re‐evaluation of its current taxonomy; insights from genetic, morphological, and ecological data. (21st October 2021) - Kiourtsoglou, Athina; Kaliontzopoulou, Antigoni; Poursanidis, Dimitris; Jablonski, Daniel; Lymberakis, Petros; Poulakakis, Nikos
Abstract: The Peloponnese wall lizard, Podarcis peloponnesiacus, is endemic to the Peloponnese. Although the phylogeny and species diversity of the Balkan species of Podarcis have been extensively studied, the intraspecific relationships of P . peloponnesiacus are not yet well defined. The aim of this study was to investigate the intraspecific diversity in this species and clarify its taxonomic status by analyzing eight gene fragments (two mitochondrial and six nuclear) and several morphological traits, typically used for systematic inferences within the genus Podarcis . Together with ecological niche modeling, we provided an integrative evaluation of the differentiation between lineages. The combination of several phylogenetic, species delimitation, and chronophylogenetic analyses revealed the existence of two highly supported and divergent clades with a distinct geographical and parapatric distribution and high niche overlap. The differentiation of the two clades dates back to the Pleistocene and is probably correlated with the paleogeography of the Peloponnese. These clades also differed in several phenotypic traits, which, however, exhibit extensive overlap and are not fully diagnostic. The combination of the above results allowed us to identify the two revealed clades as distinct species. Abstract : We investigated the intraspecific phylogenetic relationships and clarified the taxonomic status of Podarcis peloponnesiacus (endemic species to the Peloponnese, Greece) by analyzing eight gene fragments (two mitochondrial and six nuclear) and several morphological traits, together with ecological niche modeling. We consistently uncovered two, highly supported, clades within P . peloponnesiacus with distinct geographic distribution, which have diverged in Pleistocene. The combination of our results allowed us to identify the two revealed clades as distinct species: P . peloponnesiacus and P . thais .